Landmines and civilian security in Eastern Burma : implications for humanitarian engagement. - Bookbinder, Alex. (2013)
The emergence of the human security paradigm in international relations since the mid-1990s has successfully put a number of human-centric security concerns on the global agenda. The work of the International Campaign to Ban Landmines is a prominent example; its activism resulted in the 1998 Ottawa Treaty, which compels signatory states to cease manufacture, use, transfer, and stockpiling of anti-personnel landmines. However, the discourse it has promoted surrounding such devices overlooks the positive role landmines can play in protecting civilian populations from predatory national governments, as exemplified by their continued use in Eastern Burma by civilians and the non-state armed groups charged with protecting them. The use of landmines to protect civilians, while controversial and not without risks, serves to greatly improve security for populations in the context of pervasive militarization in the region. The realities of the conflict have created a difficult situation for humanitarian practitioners, who are largely unable to provide services to extremely vulnerable internally displaced populations.